Pengelolaan Toko Insolikh Mart Desa Bulontio Timur Kecamatan Sumalata Kabupaten Gorontalo Utara - Sindiawati Humena; Ellys Rachman; Sabriana Oktaviana Gintulangi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to determine the management of the Insolikh Mart Shop which is located in East Bulontio Village, Sumalata District, North Gorontalo Regency. This research uses a qualitative descriptive approach with data collection techniques in the form of interviews, observation and documentation. The results of this research indicate that product instability and relatively high levels of some non-staple goods influence consumer buying interest. The promotion carried out is not optimal, especially in the use of social media which is limited to the Facebook platform. Apart from that, stocks of goods often experience shortages, especially for products with high demand such as snacks and cosmetics. These obstacles have an impact on reducing the number of consumers and potential losses for stores. This research suggests the need for a more competitive pricing strategy, increasing the intensity of digital promotions, and a more efficient stock management system to support the growth of retail businesses in rural areas.